2017
DOI: 10.1177/1756283x17694807
|View full text |Cite
|
Sign up to set email alerts
|

Low adherence to national guidelines for proton-pump inhibitor prescription in patients receiving combination aspirin and anticoagulation

Abstract: Background:Aspirin, when used with concurrent anticoagulation, increases the risk of gastrointestinal bleeding (GIB). Therefore, multisociety guidelines recommend prophylactic proton-pump inhibitors (PPIs) for patients receiving aspirin and anticoagulation. We aimed to determine rates and predictors of adherence to these recommendations.Methods:All adult inpatients discharged from the hospital on aspirin and anticoagulation from July 2009 to June 2014 were retrospectively evaluated for PPI prescription on disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…A retrospective cohort of 2422 patients 17 published in 2017 reported that 42.2% of patients on CAT with aspirin and anticoagulants received PPI at discharge. This is comparable to the rate of 40.9% PPI co‐therapy reported in our study cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective cohort of 2422 patients 17 published in 2017 reported that 42.2% of patients on CAT with aspirin and anticoagulants received PPI at discharge. This is comparable to the rate of 40.9% PPI co‐therapy reported in our study cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Recently a study of more than 1.6 million Medicare beneficiaries showed that PPI co‐therapy resulted in 34% overall reduction in the upper GIB across warfarin, apixaban, rivaroxaban, and dabigatran 16 . Despite the current guidance and available literature, a recent retrospective single‐center study showed that only 42.2% of patients discharged on aspirin with anticoagulant therapy received a prescription for a PPI 17 . Further research is warranted to identify patients at risk for GIB and guide use of PPI in those on combined antithrombotic therapy (CAT).…”
mentioning
confidence: 99%
“…In an American study Sharma et al (6) investigated the proportion of patients prescribed PPI when discharged from the hospital on aspirin and anticoagulation. The authors found that 42.2% were prescribed a PPI at discharge and predictors for PPI co-prescribing were older age and preadmission PPI use.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Therefore, PPI therapy should be offered to patients with a true indication for antisecretory treatment. Nevertheless, it has been demonstrated that peptic ulcer prophylaxis often is lacking in patients at risk (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, in patients with atrial fibrillation (AF) who underwent recent percutaneous coronary intervention (PCI), clinical practice guidelines recommend (except in patients with a very high risk of bleeding and a low risk of ischemic events) triple antithrombotic therapy with DAPT and an anticoagulant agent. This regimen further increases the bleeding risk in this population [1,2,14]. Regarding dabigatran, a 15% decrease in drug exposure by PPI use was found in the Randomized Evaluation of Long-term Anticoagulant Therapy (RE-LY) trial, without an observable impact on efficacy or safety [15].…”
Section: Introductionmentioning
confidence: 99%